EFFICIENCYOFCOOLINGANDGASTURBINEBLADESDURABILITY - Карпінос, Б. С.; Куліш, В. М. (Science-based technologies, 2015)
Results of numerical modeling of unsteady thermal and thermostress problems of gas turbine blade model states are represented in this work.It was shown, that efficiency of dangerous blade zones modelling by means of controlled local heat transfer conditions on the surfaces of the model.There were established dependences between local temperatures and thermal stresses for the simultaneous random change of heat transfer boundary conditions for the model or for the blade. It is shown, the influence of this relationship on each thermal source can be represented by simple linear dependence with corresponding poles.An optimization method of thermocycle durability of gas turbine elements was proposed, which is based on the relation between the efficiency of blades cooling and their thermal stress stateand onthe experimental results of blade material thermal fatigue for the different temperatures.